2017
DOI: 10.1115/1.4036686
|View full text |Cite
|
Sign up to set email alerts
|

Local Changes to the Distal Femoral Growth Plate Following Injury in Mice

Abstract: Injury to the growth plate is associated with growth disturbances, most notably premature cessation of growth. The goal of this study was to identify spatial changes in the structure and composition of the growth plate in response to injury to provide a foundation for developing therapies that minimize the consequences for skeletal development. We used contrast-enhanced microcomputed tomography (CECT) and histological analyses of a murine model of growth plate injury to quantify changes in the cartilaginous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…31 Researchers frequently use wild type or transgenic mice to study orthopedic conditions. [32][33][34][35][36][37] Histological features are a gold standard to provide evidence of growth plate dysfunction. There are various parameters to evaluate abnormalities of the growth plate structure, including total height, zone height, cell density, and zone proportion.…”
Section: Histological Parameters Of the Growth Plate That Corelate With Bone Growth In Micementioning
confidence: 99%
“…31 Researchers frequently use wild type or transgenic mice to study orthopedic conditions. [32][33][34][35][36][37] Histological features are a gold standard to provide evidence of growth plate dysfunction. There are various parameters to evaluate abnormalities of the growth plate structure, including total height, zone height, cell density, and zone proportion.…”
Section: Histological Parameters Of the Growth Plate That Corelate With Bone Growth In Micementioning
confidence: 99%
“…Salter–Harris classification system divides GP fractures into five groups predicated on fracture morphology involving the physis ± epiphysis and/or metaphysis and the deleterious effect on appendicular growth 3 . Salter–Harris fractures through the physis often result in the formation of a “bony bar” bridging the epiphysis to the metaphysis 32 – 34 . In contrast, Salter–Harris type1 fractures where the cleavage plane is along the GP, preserving the RZ, heal without significant growth disturbance 3 , 4 .…”
Section: Discussionmentioning
confidence: 99%
“…As more hypertrophic chondrocytes occurred after the fibrogenic phase, the height of resting zone and hypertrophic zone increased while proliferative zone height relatively reduced. Immunohistochemistry of Col X staining also reported that Col X extends throughout the entire injury site (Drenkard et al, 2017). Furthermore, the GP injury also affects the adjacent non-injured region because injuries destroyed the controlled endochondral ossification process.…”
Section: Responses To Gp Injuries In Different Anatomical Locationsmentioning
confidence: 96%